Peran Pemerintah Dalam Meningkatkan Kesejahteraan Kelompok Tani Di Kelurahan Ompang Tanah Sirah Kecamatan Payakumbuh Utara. - Diky Wahyudi; Zuwardi Zuwardi (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
this research is the inequality of power in the farmer group system which is intertwined with the community so that each farmer group's policies carry out activities in order to achieve an increase in the production of their respective farming businesses. The aim of this research is to increase welfare. The type of research used in this research is field research with a descriptive qualitative approach. Sources of data used in this study were primary data and secondary data with farmer group informants in the village of Ompang Tanah Sirah. Data collection techniques used in this study using interviews, observation, and documentation. Data analysis techniques in this study used data reduction techniques, data presentation and drawing conclusions. The results in this study explain that some of the things that are felt by farmers after the existence of farmer groups are the provision of assistance for rice harvesting machines, business capital assistance, fertilizer assistance, everything becomes easier after the existence of groups as a medium for providing assistance. The most important thing as an indicator of welfare is income, because several aspects of household welfare depend on the level of income. As for the role played by farmer groups in the Ompang Tanah Sirah sub-district, such as being a forum for aspirations or deliberations for groups, farmer groups play a role in increasing people's income by holding economic empowerment, farmer groups play a role as a place to maintain and develop knowledge and mutual cooperation in farming among their members ( production units), hold regular meetings as a medium of communication between members of the Farmer Group, hold various trainings for the community in order to reduce unemployment and increase income.